PARP Inhibitor PJ34 Protects Mitochondria and Induces DNA-Damage Mediated Apoptosis in Combination With Cisplatin or Temozolomide in B16F10 Melanoma Cells - Cseh, Anna Maria; Fabian, Zsolt; Quintana-Cabrera, Ruben; Szabo, Aliz; Eros, Krisztian; Soriano, Maria Eugenia; Gallyas, Ferenc; Scorrano, Luca; Sumegi, Balazs (Frontiers in Physiology, 2019)
PARP-1 inhibition has recently been employed in both mono- and combination therapies in various malignancies including melanoma with both promising and contradicting results reported. Although deeper understanding of the underlying molecular mechanisms may help improving clinical modalities, the complex cellular effects of PARP inhibitors make disentangling of the mechanisms involved in combination therapies difficult. Here, we used two cytostatic agents used in melanoma therapies in combination with PARP inhibition to have an insight into cellular events using the B16F10 melanoma model. We found that, when used in combination with cisplatin or temozolomide, pharmacologic blockade of PARP-1 by PJ34 augmented the DNA-damaging and cytotoxic effects of both alkylating compounds. Interestingly, however, this synergism unfolds relatively slowly and is preceded by molecular events that are traditionally believed to support cell survival including the stabilization of mitochondrial membrane potential and morphology. Our data indicate that the PARP inhibitor PJ34 has, apparently, opposing effects on the mitochondrial structure and cell survival. While, initially, it stimulates mitochondrial fusion and hyperpolarization, hallmarks of mitochondrial protection, it enhances the cytotoxic effects of alkylating agents at later stages. These findings may contribute to the optimization of PARP inhibitor-based antineoplastic modalities.